Sampling and analysis of environmental chemical pollutants : a complete guide - Popek, Emma P. (Amsterdam ; Boston : Academic Press, 2004)
An excellent introduction to the real world of environmental work, this title helps both college students and working professionals improve their understanding of the data collection process. It covers all phases of data collection (planning, field sampling, laboratory analysis, and data quality assessment), and is a single source comprehensive reference for the resolution of the most common problems that environmental professionals face daily in their work
1. The sample and the error -- 2. Bird's eye view of project planning -- 3. Practical approach to sampling -- 4. Understanding the analytical laboratory -- 5. Data quality assessment -- Appendices -- References -- Acronyms and abbreviations -- Index.
Includes bibliographical references (pages 343-346) and index.
Keywords: Pollutants -- Analysis; Environmental sampling